The Effect of Bajakah Wood (Spatholobus Littoralis Hassk.) Extract on Carboxymethyllysine (CML) Glycation Product in Rats (Rattus Norvegicus) and its Review from an Islamic Perspective - Agfy Laila Fadhilah; Harliansyah Harliansyah; Nenden Lilis setiasih; Luh Ade Lela Arika; Puput Putuh Anisa (Eduvest - Journal of Universal Studies, 2026)
This study addresses the growing concern of skin aging associated with glycation processes, particularly the accumulation of advanced glycation end products (AGEs) such as Carboxymethyllysine (CML), which contribute to oxidative stress and tissue damage. The research aims to evaluate the effect of bajakah wood (Spatholobus littoralis Hassk.) extract on CML levels in D-galactose-induced aging model rats and to examine its relevance from an Islamic perspective. An experimental quantitative design was employed using 36 male Sprague-Dawley rats divided into six groups, including control and treatment groups receiving varying doses of bajakah wood extract. CML levels were measured using the ELISA method after treatment. The results showed that although there were variations in mean CML levels across groups, statistical analysis using One-Way ANOVA indicated no significant effect of bajakah wood extract on reducing CML levels (p > 0.05). The positive control group treated with vitamin C exhibited the lowest CML levels, while treatment groups showed fluctuating results. In conclusion, bajakah wood extract demonstrated limited in vivo antiglycation effects under the experimental conditions. However, its bioactive compounds indicate potential for further investigation, particularly with improved dosage, duration, and methodological approaches, while aligning with Islamic principles of halal and beneficial use.